A Therapeutic Approach to Premenstrual Syndrome (PMS): Modularized Treatment Program Wie kann man den Umgang mit prämenstruellen Symptomen verändern? Ein modularisiertes Behandlungsprogramm - Janda, Carolyn; Kues, Johanna N.; Kleinstäuber, Maria; Weise, Cornelia (Verhaltenstherapie, 2015)
Background: The paper presents a modularized treatment approach for women with premenstrual symptoms. Many women of reproductive age suffer from physical and/or mental premenstrual complaints, which can significantly reduce the quality of everyday life. Current studies showed positive effects of cognitive-behavioral therapy and lifestyle interventions. Overall, there is a lack of effective treatment approach. Method: The present approach addresses women with a severe premenstrual syndrome (PMS) or premenstrual dysphoric disorder (PMDD). It consists of a detailed psychoeducation, cognitive interventions regarding PMSrelated dysfunctional cognitions, strategies to change dysfunctional behaviors, and targets lifestyle issues such as stress, relaxation, balanced diet, and sports. Results: First results of the efficacy as well as the contentment with the treatment program were reported within a case study. Conclusion: The paper presents newly developed treatment guidelines, which can be integrated both, in research and therapeutic practice. The treatment guidelines should be used in further research to optimize the treatment of premenstrual burden.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Cognitive-behavioral therapy (CBT); Lifestyle habits; PMDD); Premenstrual dysphoricdisorder; Premenstrual syndrome (PMS)